Mexican Wealth Distribution 1810-1910 - Castañeda Garza, Diego (Uppsala University, 2023)
The zip files contain several files with wills from Mexico between 1810 and 1910 collected in order to measure Mexican wealth distribution in its first century of independence. The main file is wills_clean.xlsx, which contains the full collection of wills; in that file, you will find variables for year, state, and wealth, not excluding debts, debts and wealth (net wealth). You can combine this file with the do file cleaningroutine_for_social_tables to produce the detailed social tables.

The rest of the files consist of data files with the social tables (for comparison) and xlsx files with the wills from the main file divided by decade to facilitate calculations using the do file inequality_analysis_ routine_clean.do from which you will be able to reproduce the rest of the analysis (unbalanced sample and generalized beta, lognormal, etc.)

Note: The calculation programs are .do files; thus, they require stata to be executed. Some of the detailed social tables are dta files, and thus also stata files. You can open them in R and work with them or convert them to any other data format.

The wills come from 5 different Mexican archives: Archivo Histórico de Notarias de la Ciudad de México, Archivo General del Estado de Yucatán, Archivo Municipal de Saltillo, Archivo Histórico de la Ciudad de Morelia and, Testamentos del Colegio de Sonora.

ZIP-filerna innehåller flera filer med testamenten från Mexiko mellan 1810 och 1910 insamlade för att mäta mexikansk förmögenhetsfördelning under Mexikos första århundrade av självständighet. Huvudfilen är wills_clean.xlsx, som innehåller hela samlingen av testamenten; i den filen hittar du variabler för år, stat och förmögenhet, inte exklusive skulder, skulder och förmögenhet (nettoförmögenhet). Du kan använda den här filen i kombination med do-filen cleaningroutine_for_social_tables för att skapa de detaljerade sociala tabellerna.

Resten av filerna består av datafiler med sociala tabeller (för jämförelse) och xlsx-filer med testamenten från huvudfilen dividerat med decennium för att underlätta beräkningar med hjälp av do-filen inequality_analysis_ routine_clean.do från vilken du kommer att kunna reproducera resten av analysen (obalanserat prov och generaliserad beta, lognormal, etc.)
Mexikansk Förmögenhetsfördelning 1810-1910
Keywords: SOCIAL INEQUALITY; SOCIAL OJÄMLIKHET; WEALTH; FÖRMÖGENHET; wills; testamenten; ECONOMICS; EKONOMI; Economic conditions and indicators; Ekonomiska förhållanden och indikatorer; Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; Economic History; Ekonomisk historia